2021
DOI: 10.3390/ijerph18041532
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Exposure: European Citizens’ Perspectives, Trust, and Concerns on Human Biomonitoring Initiatives, Information Needs, and Scientific Results

Abstract: Over the last few decades, citizen awareness and perception of chemical products has been a topic of interest, particularly concerning national and international policy decision makers, expert/scientific platforms, and the European Union itself. To date, few qualitative studies on human biomonitoring have analysed communication materials, made recommendations in terms of biomonitoring surveillance, or asked for feedback in terms of specific biomonitoring methods. This paper provides in-depth insight on citizen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…To address public concern, citizens’ involvement was considered important to capture not just scientific but also societal and policy considerations in assessing the extent of exposure and the risk of health effects related to chemical exposure. There were two rounds of focus group discussions that were organized to obtain a better understanding of the public’s concern about chemicals and their understanding of human biomonitoring across Europe: In Austria, Portugal, Ireland, and the UK in 2018 and 2019 (the results covering analyses of discussions have been published earlier [ 7 ] (further in the text referred to as the first round of the HBM4EU focus groups); In Cyprus, Denmark, the Netherlands, Hungary, North Macedonia, Israel, and Latvia in 2020 and 2021 (further in the text referred to as the second round of the HBM4EU focus groups). …”
Section: Introductionmentioning
confidence: 99%
“…To address public concern, citizens’ involvement was considered important to capture not just scientific but also societal and policy considerations in assessing the extent of exposure and the risk of health effects related to chemical exposure. There were two rounds of focus group discussions that were organized to obtain a better understanding of the public’s concern about chemicals and their understanding of human biomonitoring across Europe: In Austria, Portugal, Ireland, and the UK in 2018 and 2019 (the results covering analyses of discussions have been published earlier [ 7 ] (further in the text referred to as the first round of the HBM4EU focus groups); In Cyprus, Denmark, the Netherlands, Hungary, North Macedonia, Israel, and Latvia in 2020 and 2021 (further in the text referred to as the second round of the HBM4EU focus groups). …”
Section: Introductionmentioning
confidence: 99%
“…Despite the above community concerns, the environmental issues surrounding the communities of Vasilikos cannot be fully addressed without the cooperation of both the established industries and the government. Previous studies have shown the mistrust of government agencies and industries [ 2 , 4 , 31 ] and the need for collaborative knowledge between citizens, experts, scientists, and policy makers on equal terms [ 8 ]. In this study, the public blamed both community authorities for wrong decisions and partial flow of information, and the government for the initiative to transform the area into an industrial hub center.…”
Section: Discussionmentioning
confidence: 99%
“…The process of understanding public perceptions about environmental health hazards, exposures, and health impacts often feeds policy making and decision support systems of public health [ 1 , 2 ]. Residents’ perceptions about environmental hazards in and around industrial contaminated areas (ICS) have always attracted attention [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. For example, the top three environmental issues of concern that may affect respondents’ health in ICS in the USA were chemicals in consumer products, outdoor air quality, and drinking water quality, while the most frequently perceived health issues were respiratory illness, asthma, and cancer [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Enough to say that human (overt and covert) behavior is at the center of concerns regarding human biomonitoring, among other areas of environmental health. Beliefs and attitudes regarding exposure to environmental contaminants, human biomonitoring health communication, community-based biomonitoring screening programs (Uhl et al, 2021), are just a few examples of areas of research and/or applied knowledge requiring the intervention of psychology thought.…”
Section: Health Psychology and Environmental Psychology: Two Worlds Apart?mentioning
confidence: 99%